UMA HISTÓRIA DE VIDA DE PAUL RICOEUR - Martins, Flávio Dantas (2018)
In this text, I intend to reflect on how Dosse's biography of Paul Ricoeur deals with problems raised by Ricoeur himself such as narrative identity, mesmity and ipseity, as well as treatment of tengely's concept of life history. Also, of course, I intend to present and recommend the work. Dosse does not require presentations in Brazil. Specialist in intellectual history and biographies, has several books translated into the Portuguese and collaborates in magazines, institutions and universities of the Atlantic. Far from moving away from the realm of biographies that many historians distrust, suspect and avoid, Dosse has become a master of the genre, including theoretical and methodological reflections on this enterprise.